ANALISIS KEUNTUNGAN PEMECAHAN SAHAM BAGI EMITEN DAN INVESTOR PADA PERUSAHAAN GO PUBLIC TERDAFTAR DI BEI PERIODE 2010 – 2013 - Herry Wira Wibawa; Hendry Ali; Wahyu Murti; Dwi Rahayu (Universitas Borobudur, 2023)
This study aims to analyze the benefits of stock splits for issuers and investors in publicly listed companies on the Indonesia Stock Exchange (BEI) from 2010 to 2013. This research is an event study to examine the influence of stock splits on changes in stock value, proxied by profitability levels, buying and selling prices, and stock trading. The results of testing the three hypotheses show that there is no significant difference in profitability levels before and after the stock split, as the average profitability levels after the stock split decreased but not significantly statistically. The second hypothesis reveals a significant difference in buying and selling prices before and after the stock split. The data analysis shows that the average buying and selling prices increased significantly after the stock split. The testing of the third hypothesis shows a significant difference in stock trading before and after the stock split. This finding proves that stock splits significantly affect the liquidity (stock trading) of shares in companies listed on the BEI from 2010 to 2013.